Can we reconcile the declarative memory and spatial navigation views on hippocampal function? - Eichenbaum, Howard; Cohen, Neal J (Neuron (Cambridge, Mass.), 2014)
Some argue that hippocampus supports declarative memory, our capacity to recall facts and events, whereas others view the hippocampus as part of a system dedicated to calculating routes through space, and these two contrasting views are pursued largely independently in current research. Here we offer a perspective on where these views can and cannot be reconciled and update a bridging framework that will improve our understanding of hippocampal function.